2021
DOI: 10.1021/acscatal.1c00165
|View full text |Cite
|
Sign up to set email alerts
|

Carbene-Catalyzed Alkylation of Carboxylic Esters via Direct Photoexcitation of Acyl Azolium Intermediates

Abstract: A carbene-catalyzed reductive coupling reaction of carboxylic esters and substituted Hantzsch esters is disclosed. Key steps of this reaction include one-electron reduction of a carbene catalyst-bound acyl azolium intermediate to generate the corresponding radical intermediate for subsequent alkylation reactions. The reaction is promoted by irradiation with visible light without the involvement of transition-metal photocatalysts. Mechanistic studies suggest that direct photoexcitation of the in situ formed acy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 66 publications
0
50
0
Order By: Relevance
“…Thus, the enolate form of the Breslow intermediate can serve as a single electron donor and an acyl radical equivalent. Since this report, a series of NHC-catalyzed radical cross-coupling reactions have been developed by us and other groups [21][22][23][24][25][26][27][28][29][30][31][32][33] . However, these reported examples have been limited to catalysis mediated by C(sp 3 )-centered radicals.…”
mentioning
confidence: 99%
“…Thus, the enolate form of the Breslow intermediate can serve as a single electron donor and an acyl radical equivalent. Since this report, a series of NHC-catalyzed radical cross-coupling reactions have been developed by us and other groups [21][22][23][24][25][26][27][28][29][30][31][32][33] . However, these reported examples have been limited to catalysis mediated by C(sp 3 )-centered radicals.…”
mentioning
confidence: 99%
“…Note that we have not observed any side‐product stemming from the reaction of NaH with the solvent [24] . Importantly, purifications involve aqueous work‐ups, indicating that acyl thiazolium salts are not as sensitive to moisture as previously suggested [8f] . We also applied this procedure to the synthesis of acyl azoliums 7 – 8 + , starting from precursors of C TN [25] and C MIC , [26] respectively.…”
Section: Resultsmentioning
confidence: 82%
“…43 Hong reported that Breslow intermediate can also be oxidized by Katritzky pyridinium salts followed by deaminative cross-coupling to forge ketones. 49 Very recently, studies from Scheidt, [51][52][53] Studer, [54][55][56][57] and our laboratories 58 found that NHC-derived azolium ester intermediates (int. II) can undergo singleelectron-reduction to generate radical intermediates for further couplings to form ketones (Figure 1b, bottom).…”
Section: Introductionmentioning
confidence: 99%
“…II) can undergo singleelectron-reduction to generate radical intermediates for further couplings to form ketones (Figure 1b, bottom). Scheidt [51][52] and our group 58 used Hantzsch esters as precursors of the other transient radical intermediates to furnish two-component coupling reactions (Figure 1c). Studer reported a tri uoromethyl radical initiated three-component coupling for the synthesis of b-Tri uoromethylated ketones (Figure 1d).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation